Sensorineural hearing loss with macrolide antibiotics exposure: a meta-analysis of the association. (16th August 2020) - Alsowaida, Yazed Saleh; Almulhim, Abdulaziz Saleh; Oh, Mok; Erstad, Brian; Abraham, Ivo
Abstract: Objective: Macrolide antibiotics are among the most commonly used antibiotics; the association of macrolide antibiotics exposure with sensorineural hearing loss (SNHL) has been hypothesized. A systematic search was conducted in PubMed, EMBASE and Cochrane Library from inception to 15 July 2019 to identify studies used macrolide antibiotics for any indication. The results were reported as odds ratio (OR) with 95% confidence interval (CI) using random-effects model to derive the association of macrolide antibiotics exposure with SNHL. The objective of this meta-analysis was to estimate the association of macrolide antibiotics exposure and SNHL from up-to-date evidence. Key findings: Nine studies met the inclusion criteria. There was no statistically significant association between macrolide antibiotics exposure and SNHL; the OR was 1.20 (95% CI: 0.96 to 1.49). No significant association was found with any of the subgroup meta-analyses. Summary: Whilst the frequency of SNHL was higher with macrolide antibiotics exposure compared with controls, overall, no association was found between macrolide antibiotics and SNHL.